(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In this work, first we studied the second-harmonic generation, preparation of high-quality CdS including CdS (cadmium powder, powder, 99.995% basis for trace minerals) on the silicon substrate in nanobelts (CdS) manufactured by Chemical Evaporation Deposition (CVD), (XRD), TEM, scanning electron microscopy (SEM), nonlinear optical properties using optical microscopy, microscopic optical measurements, and second- harmonic generation measurements using Ti: Sappire laser femto second (800 nm). The results showed that the prepared CdS nanobelts, had a blue emission and the wavelength is 400 nm, which is due to deep emissions resulting from imperfections or impurities.